2015
DOI: 10.1002/marc.201500185
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide‐b‐Poly(Phenyl Isocyanide) Hybrid Rod‐Rod Copolymers: One‐Pot Synthesis, Self‐Assembly, and Cell Imaging

Abstract: Hybrid rod-rod diblock copolymers, poly(γ-benzyl L-glutamate)-poly(4-cyano-benzoic acid 2-isopropyl-5-methyl-cyclohexyl ester) (PBLG-PPI), with determined chirality are facilely synthesized through sequential copolymerization of γ-benzyl-L-glutamate N-carboxyanhydride (BLG-NCA) and phenyl isocyanide monomers bearing chiral menthyl pendants using a Ni(cod)(bpy) complex as the catalyst in one-pot. Circular dichroism and absorption spectra reveal that each block of the block copolymers possesses a stable helical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…This result directly illustrated that the H30‐PLLA‐PPI( d ) possessed optical activity helical structures. According to our early study, the strong negative CD signal at 364 nm observed for H30‐PLLA‐PPI( d ) suggested the PPI arms possessing a predominated right‐handed helical conformation. To further elucidate the observed CD effect, two control samples were specifically prepared under identical conditions, termed as H30‐PLLA‐PPI( l ) and racemic H30‐PLLA‐PPI( l / d ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…This result directly illustrated that the H30‐PLLA‐PPI( d ) possessed optical activity helical structures. According to our early study, the strong negative CD signal at 364 nm observed for H30‐PLLA‐PPI( d ) suggested the PPI arms possessing a predominated right‐handed helical conformation. To further elucidate the observed CD effect, two control samples were specifically prepared under identical conditions, termed as H30‐PLLA‐PPI( l ) and racemic H30‐PLLA‐PPI( l / d ).…”
Section: Resultsmentioning
confidence: 86%
“…Water was deionized with a Milli‐Q SP reagent water system (Millipore) to a specific resistivity of 18.0 MΩ cm. The optically active phenyl isocyanide monomers ( l ‐PI and d ‐PI) bearing a different chiral pendant were directly used as the same batch in our previously reported work …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhodamine-encoded bifunctional catalyst ClPd(PEt 3 ) 2 -RhB-OH bearing a Pd(II) active center and a hydroxyl group was synthesized from rhodamine B hydrochloride by sequential chemical modification (scheme S1a) 31, 33-35. The chemical structure of the intermediates (1-8) during the catalyst preparation were verified by 1 H NMR spectra, and the exact structure of the final ClPd(PEt 3 ) 2 -RhB-OH was confirmed by 1 H NMR, 13 C NMR, 31 P NMR, mass spectrometry (Figure S1), and FT-IR spectrometry (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…We envision that PPI is very attractive for IR-780 micelles due to two main reasons: (1) with a distinctive π-conjugated system, PPI has an inherently stable helical conformation in aqueous solution or in solid state, which has a structural similarity to CPPs 30, 31. Therefore, introducing hydrophilic helical PPI chains in the micelle shell would facilitate intracellular delivery of cargos and create an artificial synthetic helical polymer-based delivery system.…”
Section: Introductionmentioning
confidence: 99%